Biosynthetic Pathway for the Epipolythiodioxopiperazine Acetylaranotin in Aspergillus terreus Revealed by Genome-Based Deletion Analysis - Guo, Chun-Jun; Yeh, Hsu-Hua; Chiang, Yi-Ming; Sanchez, James F; Chang, Shu-Ling; Bruno, Kenneth S; Wang, Clay C. C (Journal of the American Chemical Society, 2013)
Epipolythiodioxopiperazines (ETPs) are a class of fungal secondary metabolites derived from diketopiperazines. Acetylaranotin belongs to one structural subgroup of ETPs characterized by the presence of a seven-membered 4,5-dihydrooxepine ring. Defining the genes involved in acetylaranotin biosynthesis should provide a means to increase the production of these compounds and facilitate the engineering of second-generation molecules. The filamentous fungus Aspergillus terreus produces acetylaranotin and related natural products. Using targeted gene deletions, we have identified a cluster of nine genes (including one nonribosomal peptide synthetase gene, ataP) that is required for acetylaranotin biosynthesis. Chemical analysis of the wild-type and mutant strains enabled us to isolate 17 natural products from the acetylaranotin biosynthesis pathway. Nine of the compounds identified in this study are natural products that have not been reported previously. Our data have allowed us to propose a biosynthetic pathway for acetylaranotin and related natural products.